Les offices « populaires » du gouvernement municipal de Naples à l’époque moderne - Brigitte Marin; Piero Ventura (Mélanges de la Casa de Velázquez)
In the Modern Age, local government in Naples rested upon a clear distinction between nobles and «people». The «popular» offices are still little known, for a large proportion of the municipal archives have been destroyed. This article therefore seeks to retrace the organisation of «popular» local powers, characterised by a close political relationship with the Crown as from the close of the Aragonese period. In order to gain a better understanding of this linkage between royal power and «popular» citizen government, the study attempts to more clearly outline the figure of the People’s Representative, who discharged first-rate functions in the city’s administration and who was closely tied to Viceroy under Spanish dominion, then later to the King himself under the Bourbons. The captains of the ottine, appointed by the assemblies of family heads of the twenty-nine quarters, played an essential role as mediators between the citizenry and the municipal or the royal authority, as well as providing a measure of social control. The article analyses the evolution of this office up to the creation of the royal police in 1780.